Collagen crosslinking with conventional and accelerated ultraviolet‐A irradiation using riboflavin with hydroxypropyl methylcellulose. Issue 4 (April 2017) - Hagem, Anne Marie; Thorsrud, Andreas; Sandvik, Gunhild Falleth; Råen, Marianne; Drolsum, Liv
Abstract : Purpose : To evaluate corneal collagen crosslinking (CXL) with conventional and accelerated ultraviolet‐A (UVA) irradiation using riboflavin with methylcellulose. Setting : Department of Ophthalmology, Oslo University Hospital, Oslo, Norway. Design : Prospective randomized case series. Methods : Patients with keratoconus were randomized to have CXL using conventional 3 mW/cm 2 UVA irradiation for 30 minutes (CXL30) or accelerated 9 mW/cm 2 UVA irradiation for 10 minutes (CXL10). In both groups, a solution of riboflavin 0.1% with hydroxypropyl methylcellulose 1.1% (methylcellulose–riboflavin) was used. The endothelial cell density (ECD), visual acuity, and tomography were measured at baseline and after 12 months. Anterior segment optical coherence tomography and in vivo confocal microscopy (IVCM) were performed after 1 month. Results : The study comprised 40 patients (40 eyes). A complete absence of keratocytes in all eyes at 100 μm depths was found on IVCM. At 300 μm, 400 μm, and preendothelial levels, the differences were 83.3% versus 31.3% ( P = .02), 64.7% versus 20.0% ( P = .01), and 42.1% versus 5.9% ( P = .02) in the CXL30 and CXL10 groups. No statistically significant differences were found in the change in visual acuity or maximum keratometry between the groups after 12 months. There was no relationship between the depth of keratocyte absence and the ECD change after 12 months. Conclusions : Marked deep structural changes with an absence of keratocytes occurred when CXL was used with conventional or accelerated UVA irradiation; however, the changes were more pronounced with the use of conventional UVA irradiation. The use of methylcellulose–riboflavin might explain the deep alterations and raises a long‐term safety concern.